2019
DOI: 10.1136/openhrt-2018-000945
|View full text |Cite
|
Sign up to set email alerts
|

A zero coronary artery calcium score in patients with stable chest pain is associated with a good prognosis, despite risk of non-calcified plaques

Abstract: ObjectivesTo estimate the prevalence of non-calcified coronary artery disease (CAD) in patients with suspected stable angina and a zero coronary artery calcification (CAC) score, and to assess the prognostic significance of a zero CAC in these symptomatic patients.MethodsIn this prospective cohort study, consecutive patients with stable chest pain underwent CAC scoring ± CT coronary angiography (CTCA) as part of routine clinical care at a single tertiary centre over 7 years. Major adverse cardiac event (MACE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 15 publications
4
35
1
1
Order By: Relevance
“…A CACS of 0 was the strongest marker of MACE in this study. Our results are consistent with those from previous reports [2,3,14] and indicate that patients with a CACS of 0 show a good prognosis. The incidence of MACE in the present study was higher than that in previous reports [3,14].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A CACS of 0 was the strongest marker of MACE in this study. Our results are consistent with those from previous reports [2,3,14] and indicate that patients with a CACS of 0 show a good prognosis. The incidence of MACE in the present study was higher than that in previous reports [3,14].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with those from previous reports [2,3,14] and indicate that patients with a CACS of 0 show a good prognosis. The incidence of MACE in the present study was higher than that in previous reports [3,14]. Kim et al reported that the incidence of MACE in CACS = 0 and CACS > 0 groups was 1.3% and 4.7% over 2.8 years, respectively [14].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations